2014
DOI: 10.1016/j.biocel.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Cx26 regulates proliferation of repairing basal airway epithelial cells

Abstract: The recovery of an intact epithelium following injury is critical for restoration of lung homeostasis, a process that may be altered in cystic fibrosis (CF). In response to injury, progenitor cells in the undamaged areas migrate, proliferate and re-differentiate to regenerate an intact airway epithelium. The mechanisms regulating this regenerative response are, however, not well understood. In a model of circular wound injury of well-differentiated human airway epithelial cell (HAEC) cultures, we identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Double positive CK14/ p63-positive basal cells are rare in the airway and such cells have been associated with injury or wound-healing responses. 42 Interestingly, Oh et al 22 have shown that primary human keratinocytes transfected with ΔNp63 underwent EMT when they had depleted their normal proliferative capacity. Thus, injury-response CK14/p63-positive cells in the epithelium overlying the fibroblastic foci could be a cellular source for EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Double positive CK14/ p63-positive basal cells are rare in the airway and such cells have been associated with injury or wound-healing responses. 42 Interestingly, Oh et al 22 have shown that primary human keratinocytes transfected with ΔNp63 underwent EMT when they had depleted their normal proliferative capacity. Thus, injury-response CK14/p63-positive cells in the epithelium overlying the fibroblastic foci could be a cellular source for EMT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CFTR plays a critical role in this mechanism. Although it is not clear whether a defective CFTR decreases or enhances wound healing, many studies show that bronchial epithelial cells lacking CFTR are not able to reconstitute a fully differentiated epithelium [110112]. …”
Section: Role Of Cftr In the Lungsmentioning
confidence: 99%
“…We focused on 3 connexins (Cx26, Cx30, and Cx43) that have been implicated in acute and chronic inflammation, wound healing, and in lower airway pathology . Connexin investigations in diabetic wounds have revealed elevated levels of Cx26 and Cx43 in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%